Towards energy-efficient 5G networks: coordination solutions for macro and pico cells - Hasanah Putri; Rendy Munadi; Sofia Naning Hertiana; Alfin Hikmaturokhman (Bulletin of Electrical Engineering and Informatics, 2026)
The increasing demand for high-speed, low-latency connectivity has driven the rapid deployment of fifth-generation (5G) networks. However, the enhanced performance of 5G systems comes at the cost of higher energy consumption, posing a significant challenge to sustainability goals. This study explores energy-efficient coordination strategies for macro and pico cells to optimize power usage while maintaining network performance. By employing a systematic mapping study (SMS) and a systematic literature review (SLR), we analyze current research trends, challenges, and emerging solutions in energy-efficient 5G network design. Key strategies, including AI-driven resource allocation, dynamic spectrum management, and interference mitigation techniques, are examined to assess their effectiveness in reducing energy consumption. The findings highlight the critical role of intelligent coordination mechanisms in achieving a balance between energy efficiency and service quality. This research contributes to the development of sustainable 5G architectures by identifying optimal methodologies for macro- and pico-cell integration, paving the way for greener and more adaptive next-generation networks.